1998
DOI: 10.1093/jjco/28.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Expression of the Vascular Endothelial Growth Factor in Human Non-small-cell Lung Cancers

Abstract: Background: Angiogenesis is an essential factor for progression and metastases in solid tumors. It has been reported that several angiogenic factors playa role in the regulation of angiogenesis. Vascular endothelial growth factor (VEGF) is one of the most important molecules in angiogenesis. We investigated expressions of VEGF in a series of lung carcinomas with regard to clinicopathological factors. Method: VEGF expression was investigated by use of immunohistochemical studies and Northern blot analysis, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 19 publications
5
50
1
1
Order By: Relevance
“…However, an earlier study found variable serum Ang-1 levels according to different types of cancers [25]. In tissue studies, Ang-1 is upregulated in various malignancies, with a few exceptions [22,29,38]. In lung cancer tissues, the expression pattern of Ang-1 is variable and its clinical significance is controversial [19,22,24,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an earlier study found variable serum Ang-1 levels according to different types of cancers [25]. In tissue studies, Ang-1 is upregulated in various malignancies, with a few exceptions [22,29,38]. In lung cancer tissues, the expression pattern of Ang-1 is variable and its clinical significance is controversial [19,22,24,39].…”
Section: Discussionmentioning
confidence: 99%
“…In tissue studies, Ang-1 is upregulated in various malignancies, with a few exceptions [22,29,38]. In lung cancer tissues, the expression pattern of Ang-1 is variable and its clinical significance is controversial [19,22,24,39]. The overall contradictory findings regarding Ang-1 expression may not be explained adequately by the differences in laboratory methodologies and study populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that Ang1 as well as Ang2 were direct substrates in endothelial cell adhesion mediated by integrins (Carlson et al, 2001). Many studies have investigated the expression patterns of Ang1, other angiopoietins, and Tie2 in a variety of tumours, including cancers of the breast (Hayes et al, 2000;Currie et al, 2001), brain (Stratmann et al, 1998;Zagzag et al, 1999;Eggert et al, 2000), liver (Tanaka et al, 1999), ovary (Martoglio et al, 2000), lung (Takahama et al, 1999;Wong et al, 2000), Kaposi's sarcoma and cutaneous angiosarcoma , thyroid gland (Bunone et al, 1999), and leukaemia (Kukk et al, 1997). These studies revealed a complex pattern of expression of the angiopoietins and Tie2 that is consistent with an important role for Ang2 and VEGF in the destabilization of vasculature and initiation of tumour angiogenesis.…”
mentioning
confidence: 99%